Social inclusion among young adults with mental illness and complex needs in Flexible Assertive Community Treatment: A qualitative study on team staff’s understanding and experiences - Silje Nord-Baade; Ottar Ness; Michael Rowe; Camilla Bergsve Jensen; Anne Landheim (PLoS ONE, 2026)
Background Social inclusion is increasingly highlighted through policies, practices, research, and broader societal awareness. Young adults with mental illness and complex needs are among the most marginalized in society and face significant challenges. Public health and welfare services play a critical role in either facilitating or hindering social inclusion through adequate or inadequate service provision. The services are often critiqued for treating individuals in isolation from their social contexts. Methods In this qualitative study semi-structural individual interviews and thematic analysis were used to explore: How do service providers in FACT teams understand and promote social inclusion among young adults with mental illness and complex needs?. Results The results showed that staff employed efforts to promote social inclusion and acknowledged this as important. However, they had limited conceptual understanding and revealed a lack of systematic promotion in the teams. Several barriers for social inclusion were evident in the material, from individual and structural to societal. Conclusions There is a need to develop and operationalize the concept to enable systematic and holistic approaches to promote social inclusion, moving beyond employing single interventions. Policies must be developed, and training and education provided to create context sensitive mental health services.